Post-Thaw Storage Temperature Influenced Boar Sperm Quality and Lifespan through Apoptosis and Lipid Peroxidation - Junwei Li; Juncheng Li; Shuaibiao Wang; Huiming Ju; Shufang Chen; Athina Basioura; Graça Ferreira-Dias; Zongping Liu; Jiaqiao Zhu (Animals, 2023)
Cryopreservation deteriorates boar sperm quality and lifespan, which restricts the use of artificial insemination with frozen-thawed boar semen in field conditions. The objective of this study was to test the effects of post-thaw storage time and temperature on boar sperm survival. Semen ejaculates from five Landrace boars (one ejaculate per boar) were collected and frozen following a 0.5 mL-straw protocol. Straws from the five boars were thawed and diluted 1:1 (v:v) in BTS. The frozen-thawed semen samples were aliquoted into three parts and respectively stored at 5 °C, 17 °C, and 37 °C for up to 6 h. At 0.5, 2, and 6 h of storage, sperm motility, viability, mitochondrial membrane potential, and intracellular reactive oxygen species (ROS) levels and apoptotic changes were measured. Antioxidant and oxidant levels were tested in boar sperm (SPZ) and their surrounding environment (SN) at each timepoint. The results showed significant effects of post-thaw storage time and temperature and an impact on boar sperm quality (total and progressive motility, VCL, viability, acrosome integrity), early and late sperm apoptotic changes, and changes in MDA levels in SPZ and SN. Compared to storage at 5 °C and 37 °C, frozen-thawed semen samples stored at 17 °C displayed better sperm quality, less apoptotic levels, and lower levels of SPZ MDA and SN MDA. Notably, post-thaw storage at 17 °C extended boar sperm lifespan up to 6 h without obvious reduction in sperm quality. In conclusion, storage of frozen-thawed boar semen at 17 °C preserves sperm quality for up to 6 h, which facilitates the use of cryopreserved boar semen for field artificial insemination.